2013
DOI: 10.1111/acps.12096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating interventions to improve somatic health in severe mental illness: a systematic review

Abstract: Many interventions directed toward improving somatic health for patients with SMI have been started. These studies did not apply similar evaluations, and did not use uniform outcome measures of the effect of their interventions. Valuable comparisons on effectiveness are therefore almost impossible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…A systematic review showed that the numbers of randomized controlled trials to evaluate interventions to improve somatic health in severe mental illness was limited, indicating a need for further controlled studies to identify the optimal interventions [111]. Previous reviews had shown that the quality of the preventive and screening services for somatic disorders received by patients with mental illness was often lower, but occasionally superior to that received by persons with no mental disorder [61].…”
Section: Screening For Physical Disorders In Patients With Mental Dismentioning
confidence: 99%
“…A systematic review showed that the numbers of randomized controlled trials to evaluate interventions to improve somatic health in severe mental illness was limited, indicating a need for further controlled studies to identify the optimal interventions [111]. Previous reviews had shown that the quality of the preventive and screening services for somatic disorders received by patients with mental illness was often lower, but occasionally superior to that received by persons with no mental disorder [61].…”
Section: Screening For Physical Disorders In Patients With Mental Dismentioning
confidence: 99%
“…Metabolic syndrome, a constellation of risk factors for cardiovascular disease is positively associated with symptom severity in depression . Interventions to improve somatic health in mental illness frequently target risk factors for cardiovascular disease .…”
Section: Introductionmentioning
confidence: 99%
“…SMI has been found to be associated with obesity, smoking, diabetes mellitus, hypertension and metabolic syndrome [10,14,39], and generally the prevalence of CVDs risk factors among people with SMI is high [40]. However, obesity and hypertriglyceridemia do not seem inherent to SMI, since it can be effectively managed by specific interventions, including dietary education and physical activity [41], but also other types of interventions such as health education, smoking cessation, and changes in health care organization [42]. Indeed also a relatively recent meta-analysis found that only diabetes mellitus was strongly associated with SMI, while hypertension and dyslipidemia were with severe mental illness in Italy not, even if studies about the latter two factors were too heterogeneous or inadequate to draw firm conclusions [7].…”
Section: Main Findingsmentioning
confidence: 99%